Pharmacokinetics of Active Components From Guhong Injection in Normal and Pathological Rat Models of Cerebral Ischemia: A Comparative Study - Yu, Li; Wan, Hao-fang; Li, Chang; Yang, Jie-hong; Zhou, Hui-fen; Wan, Hai-tong; He, Yu (Frontiers in Pharmacology, 2018)
Background and Objectives: Guhong Injection (GHI) is usually administered for the treatment of stroke in clinics. Aceglutamide and hydroxyl safflower yellow A (HSYA) are its key ingredients for brain protective effect. To investigate the pharmacokinetics of aceglutamide and HSYA under pathological and normal conditions, the pharmacokinetic parameters and characteristics of middle cerebral artery occlusion (MCAO) and normal rats given the same dosage of GHI were studied compared. Methods: 12 SD rats were divided into two groups, namely, MCAO and normal groups. Both groups were treated with GHI in the same dosage. Plasma samples were collected from the jaw vein at different time points and subsequently tested by high-performance liquid chromatography (HPLC). Results: After administration of GHI, both aceglutamide and HSYA were immediately detected in the plasma. Ninety percent of aceglutamide and HSYA was eliminated within 3 h. For aceglutamide, statistically significant differences in the parameters including AUC(0−t), AUC(0−∞), AUMC(0−t), AUMC(0−∞), Cmax (P < 0.01), and Vz (P < 0.05). Meanwhile, compared with the MCAO group, in the normal group, the values of AUC(0−t), AUMC(0−t), VRT(0−t), and Cmax (P < 0.01) for HSYA were significantly higher, whereas the value of MRT(0−t) was significantly lower in the normal group. Conclusions: The in vivo trials based on the different models showed that, the pharmacokinetic behaviors and parameters of aceglutamide and HSYA in GHI were completely different. These results suggest that the pathological damage of ischemia-reperfusion has a significant impact on the pharmacokinetic traits of aceglutamide and HSYA.